2020
DOI: 10.21595/jmeacs.2020.21814
|View full text |Cite
|
Sign up to set email alerts
|

Vibration research of heavy trucks. Part 2: Optimization of vehicle dynamic parameters

Abstract: In order to enhance the ride comfort, stability, and safety of heavy trucks. Based on the dynamic characteristics of the parameters of heavy trucks and its dynamic model, a multi-objective genetic algorithm are developed in the MATLAB environment and applied to optimize the dynamic parameters of vehicles. The weighted root-mean-square (RMS) accelerations of the cab and driver seat vibrations are chosen as the study goals to evaluate the results under different vehicle conditions. The obtained results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Mahmoodabadi et al [1] applied the genetic algorithm (GA) for improving the ride quality of the model of half-vehicle, while Li and Wang [2][3] built the dynamic model of the half-vehicles for simulating and optimizing the parameters of the cab's suspension systems to decrease the seat's vibration in the vertical direction. Chen et al [4] also applied measurement and simulation methods to optimize the cab's isolation system for heavy commercial vehicles. In addition, Zhang et al [5] had researched a dynamic model of the multi-body for the isolating systems of the cab to reduce the RMS accelerations of the vertical driver's seat and cab pitch angle.…”
Section: Introductionmentioning
confidence: 99%
“…Mahmoodabadi et al [1] applied the genetic algorithm (GA) for improving the ride quality of the model of half-vehicle, while Li and Wang [2][3] built the dynamic model of the half-vehicles for simulating and optimizing the parameters of the cab's suspension systems to decrease the seat's vibration in the vertical direction. Chen et al [4] also applied measurement and simulation methods to optimize the cab's isolation system for heavy commercial vehicles. In addition, Zhang et al [5] had researched a dynamic model of the multi-body for the isolating systems of the cab to reduce the RMS accelerations of the vertical driver's seat and cab pitch angle.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the ride comfort of vehicles has always been of particular interest to researchers. To study this issue in detail, the influence of the vehicle's design parameters as well as the suspension system had been analyzed and evaluated [1][2][3]. Optimizing the design parameters of the suspension systems had been made to improve the ride comfort [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…To study this issue in detail, the influence of the vehicle's design parameters as well as the suspension system had been analyzed and evaluated [1][2][3]. Optimizing the design parameters of the suspension systems had been made to improve the ride comfort [1,4]. Studies showed that the vehicle's ride comfort had been significantly improved.…”
Section: Introductionmentioning
confidence: 99%